The components of personal passports for people living with dementia in an acute healthcare setting: an integrative review. Issue 13 (25th February 2021) - Beattie, Fiona; Kerr, Lisa; Larkin, John; Cawley, Des
Abstract: Aim: To explore the components of personal passports for people living with dementia in an acute healthcare setting. Background: Globally, supporting people with dementia poses a prominent health and social care challenge. Importance for people with dementia in an acute healthcare setting includes social relationships and communication with healthcare staff. A personal passport is an international initiative designed to support the personhood of the person living with dementia. Methods: This integrative review is based on the methodology of Whittmore and Knafl (2005). The Preferred Reporting for Systematic Reviews and Meta‐Analyses (PRISMA) guidelines and checklist were adhered to. A database search of PubMed, MEDLINE, CINAHL, Scopus and EBSCO databases was systematically performed. Results: This integrative review identified nine research studies on the components of personal passports that met the inclusion and exclusion criteria. A constant comparative method of data analysis identified five key pivotal themes: person‐centredness, communication, family/carer involvement, education and leadership. Conclusion: The use of personal passports supports the provision of person‐centred care for people living with dementia through enhancing the well‐being of both the person and their families/caregivers. Relevance to clinical practice: Personal passports are an important document and should be determined by the person with dementia, their care needs and the caregiver's role in meeting these needs.